2019
DOI: 10.2147/ijn.s205574
|View full text |Cite
|
Sign up to set email alerts
|

<p>A brief review of cytotoxicity of nanoparticles on mesenchymal stem cells in regenerative medicine</p>

Abstract: Multipotent mesenchymal stem cells have shown great promise for application in regenerative medicine owing to their particular therapeutic effects, such as significant self-renewability, low immunogenicity, and ability to differentiate into a variety of specialized cells. However, there remain certain complicated and unavoidable problems that limit their further development and application. One of the challenges is to noninvasively monitor the delivery and biodistribution of transplanted stem cells during trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 236 publications
(191 reference statements)
0
20
0
Order By: Relevance
“…The two cutting-edge fields of iPSCs and nanoparticles empower the cross-field development of novel techniques. The possible limitation may come from the cytotoxicity of nanoparticles, which results from the accumulation of nanoparticles in endosomes and/or vacuoles in cells [ 133 , 134 ]. However, iron oxide nanoparticles will be degraded through normal iron metabolism over time, although the mechanism is still not well understood [ 19 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two cutting-edge fields of iPSCs and nanoparticles empower the cross-field development of novel techniques. The possible limitation may come from the cytotoxicity of nanoparticles, which results from the accumulation of nanoparticles in endosomes and/or vacuoles in cells [ 133 , 134 ]. However, iron oxide nanoparticles will be degraded through normal iron metabolism over time, although the mechanism is still not well understood [ 19 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MSCs have been used for the in vitro and in vivo delivery of, among others, diagnostic and therapeutic agents, small interfering RNA and nanoparticles [57]. In particular, several authors have shown that MSCs easily internalize different types of nanoparticles [27] and can reach the tumor, showing limited or no toxicity effect of NPs to MSCs [58,59]. Additionally, other authors have investigated whether MSCs can transport nanoparticles for therapeutic purposes [22,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…These cells are then internalized by endocytosis [ 115 ]. Quantum dots can also be used for monitoring the living cells for a long time [ 116 , 117 ].…”
Section: Applications Of Nanotechnology In Healthcare Sectorsmentioning
confidence: 99%